2019
DOI: 10.1097/htr.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Quality Appraisal of Systematic Reviews for Behavioral Treatments of Attention Disorders in Traumatic Brain Injury

Abstract: Objective: This review appraised the quality of systematic reviews (SRs) and meta-analyses (MAs) to summarize research on behavioral interventions for attention disorders in persons with traumatic brain injury. Methods: A search of 7 databases revealed 15 MAs/SRs reporting outcomes for attention treatments in traumatic brain injury. Two examiners independently coded the quality of reviews with the Critical Appraisal of Systematic Review or Meta-Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…As a retrospective chart review, the study did not use control subjects, and therefore obtaining measures of M 1 and M 2 are not directly available. However, several studies have determined that the estimated change in cognitive test-retest scores ranges between 0.25 and 0.33 of a typical standard deviation [ 29 , 31 ]. Applied to standard scores, M 1 , M 2 values would range between 3.75 and 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…As a retrospective chart review, the study did not use control subjects, and therefore obtaining measures of M 1 and M 2 are not directly available. However, several studies have determined that the estimated change in cognitive test-retest scores ranges between 0.25 and 0.33 of a typical standard deviation [ 29 , 31 ]. Applied to standard scores, M 1 , M 2 values would range between 3.75 and 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…The RCI technique used to correct for practice effects and measurement error is defined as (( X 2 − X 1 − ( M 2 − M 1 ))/SDD [74,75] where X 1 is the measured pretest score, X 2 the post-test score, SDD the standard deviation of the group test-retest difference, X 1 the control group mean pretest score, and X 2 the control group mean post-test score. As a retrospective chart review, the study did not use control subjects and therefore obtaining measures of M 1 and M 2 are not directly available.…”
Section: Methodsmentioning
confidence: 99%
“…As a retrospective chart review, the study did not use control subjects and therefore obtaining measures of M 1 and M 2 are not directly available. However, several studies have determined that the estimated change in cognitive test retest scores range between .25 and .33 of a typical standard deviation [74-76]. Applied to standard scores, M 1 M 2 values would range between 3.75 and 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen of those reviews demonstrated effectiveness (Bogdanova et al, 2016;Cicerone et al, 2005;Cicerone et al, 2011;Elliott and Parente, 2014;Fritz, Cheek, and Nichols-Larsen, 2015;Hallock et al, 2016;Kennedy et al, 2008;Lambez and Vakil, 2021;Little, Byrne, and Coetzer, 2021;O'Neil-Pirozzi, Kennedy, and Sohlberg, 2016;Park, Maitra, and Martinez, 2015;Radomski et al, 2016;Rodríguez-Rajo et al, 2018;Rohling et al, 2009), and two demonstrated no effect Virk et al, 2015). Additionally, three reviews had mixed findings (Cicerone et al, 2019;Roitsch et al, 2019;Steel, Elbourn, and Togher, 2021), and four characterized the evidence as uncertain (Ali, Viczko, and Smart, 2020;Brassel et al, 2021;Geraldo et al, 2018;Schrijnemaekers et al, 2014). Two systematic reviews assessed the effect of behavioral rehabilitation on cognitive outcomes, demonstrating effectiveness in the general adult population (Little, Byrne, and Coetzer, 2021) and uncertain conclusions in populations restricted to veterans (Wilson et al, 2016).…”
Section: Cognitivementioning
confidence: 99%